Morphological Changes in the Blood Vessels of the Femoral Head in Rats Under the Influence of Glucocorticosteroids (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This study examined morphological changes in the vascular tissues of the femoral head in rats following the administration of glucocorticosteroids (GCS). Dexamethasone was selected as the GCS agent. Histological and histochemical methods were used for morphological analysis. The results revealed vasculopathic changes in the microcirculatory system of the femoral head, endothelial degradation, and microthrombosis under the influence of GCS.